A Novel Floating Memristor Emulator with Minimal Components. (19th October 2017) - Li, Zhijun; Zeng, Yicheng; Ma, Minglin
Abstract : A new floating emulator for the flux-controlled memristor is introduced in this paper. The proposed emulator circuit is very simple and consists of only two current feedback operational amplifiers (CFOAs), two analog multipliers, three resistors, and two capacitors. The emulator can be configured as an incremental or decremental type memristor by using an additional switch. The mathematical model of the emulator is derived to characterize its behavior. The hysteresis behavior of the emulator is discussed in detail, showing that the pinched hysteresis loops inv -i plane depend not only on the amplitude-to-frequency ratio of the exciting signal but also on the time constant of the emulator circuit itself. Experimental tests are provided to validate the emulator's workability.